Allyson Clay : Imaginary Standard Distance. - Walter Philips Gallery, Banff; Mount Saint Vincent University Art Gallery, Halifax; Art Gallery of Greater Victoria, Victoria; Kamloops Art Gallery, Kamloops (Banff : Walter Phillips Gallery - The Banff Centre for the Arts, 2002)
This exhibition is a mid-career retrospective of the work of Vancouver-based artist Allyson Clay. It is texturally rich and includes artworks ranging from painting to video. Clay's work is both seductive and challenging, negotiating the margins between curiosity and voyeurism that is currently receiving widespread attention in popular culture.
biog., ind. tent., gr. tent., bibliog. p. 43-45
Engels
Allyson Clay : Imaginary Standard Distance, Walter Phillips Gallery, The Banff Center, April 13 - May 26, 2002 / Mount Saint Vincent University Art Gallery, Halifax, October 20 - November 24, 2002 / Art Gallery of Greater Victoria, Victoria, September 9 - November 14, 2004 / Kamloops Art Gallery, Kamloops, December 12, 2004 - January 30, 2005
boek
Keywords: Clay, Allyson